Mapping out the response sequence of the sprint start - Crotty, E. D.; Furlong, L.-A. M.; Harrison, A. J.; Milloz, M. (ISBS Proceedings Archive (Michigan), 2023)
Establishing the limits of sprint start response time (SSRT) requires the mapping of the muscular sequence of activation and mechanical response delays and was the aim of the current study. Sprint start performance of 15 sprinters was examined with kinematic, EMG, and block force data collected. A general muscle activation sequence was identified, with both deltoid muscles, the rear leg rectus femoris, and the rear leg tibialis anterior the first muscles to increase activation from the set position. With ankle dorsiflexion the initial motion during the block push, examining the period between tibialis anterior muscle onset and block force onset is critical for quantifying mechanical response delays . Estimates of this delay period were as low as 7 ms which has implications for our understanding of the minimum SSRT a sprinter can legally produce.